An observational study of abnormal findings in fetus during 11-13+6 weeks and targeted imaging for fetal anomalies ultrasonography - Patel, Amrita D.; Shingadia, Janki B.; Patel, Devang (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Congenital anomalies are responsible for a of 14.2% of perinatal mortality in India. This study focuses on incidence of structural fetal abnormalities detected during 1st and 2nd trimester sonography. Aim of this study was to evaluate the need for targeted fetal scans. Methods: This study is an observational study conducted at Gujarat fetal medicine Centre, Ahmedabad, Gujarat, super specialty antenatal radiology centre where exclusively antenatal USGs and prenatal procedures are performed. All pregnant female coming for 1st and 2nd trimester USG were included. All fetal abnormalities in form of soft markers and structural abnormality were included. Results: Out of 2122 total ANC scans, 183 cases (8.6%) had structural abnormality and 235 cases (11%) had significant soft markers. 1185 cases (55.84%) came in late 2nd trimester for TIFFA scan and 468 (22%) were seen in 1st trimester scan. The incidence of fetal anomaly in this study was higher than general population as it is an exclusively fetal medicine centre and majority of patients were diagnosed with anomaly in late 2nd trimester. Conclusions: There is immense need for early diagnosis and timely intervention before 20 weeks in case of prenatal detection of fetal abnormality.